Antimicrobial peptide from lactic acid Bacteria and development of antimicrobial film for food packaging - Weerapong Woraprayote (Prince of Songkla University, 2015)
Thesis (Ph.D., (Food Science and Technology))--Prince of Songkla University, 2014